Quantitative criminology in the United Kingdom in the 1990s: A brief overview - Farrington, David (Journal of quantitative criminology, 1996)
Quantitative criminology research published in the United Kingdom (England, Wales, Scotland, and Northern Ireland) in the 1990s is reviewed. Publications are divided into five topical categories: measurement; explanations or correlates; police or crime prevention; sentencing; and correctional treatment. The most sophisticated studies are on longitudinal and criminal career research, correlates of victimization, quasi-experimental analysis of policing strategies, prediction of reconviction and sentencing, and evaluation of correctional treatment using statistical controls. More fundamental long-term research on the causes of crime is needed, together with more concern for reliability and validity issues, and more evaluation research including controls for extraneous variables using quasiexperimental or (preferably) experimental techniques.